MOMENT TENSOR DETERMINATION USING A NEW WAVEFORM INVERSION TECHNIQUE - Moshou, A.; Papadimitriou, P.; Makropoulos, K. (Bulletin of the Geological Society of Greece, 2010)
In this study a new waveform inversion methodology was developed to determine the source parameters of an earthquake. This technique is based on analyzing data recorded both at teleseismic and regional distances. To apply the inversion three different methods, which are the normal equations, the QR-decomposition and the singular value decomposition (SVD), were successfully tested, similar results were obtained and the SVD method was selected. The proposed inversion methodology was applied to large, as well as to earthquakes of moderate magnitude. Analysis of moderate events is crucial for seismogenic volumes, where an important number of such earthquakes occur which allow the calculation of their source parameters. Thus, the seismotectonic characteristics of the study area can be determined. The proposed methodology is successfully applied to events located in Greece and its surrounding regions in near real time.